Can Sociodemographic Factors be Used to Help Predict Outcomes in Charcot Neuroarthropathy? - Brandon J. Martinazzi BS; Kirsten N. Mansfield; Kelly Dopke; Anna Ptasinski; Chris M. Stauch BS; Zachary Koroneos BS; Hannah Nam; Gregory Kirchner; Michael C. Aynardi MD (Foot & Ankle Orthopaedics, 2022)
Category: Diabetes; Other Introduction/Purpose: The diabetic Charcot foot, or Charcot neuroarthropathy, is a devastating condition that arises secondary to longstanding diabetes, peripheral neuropathy, and trauma. One of the many challenges associated with the Charcot patient is the lack of data exploring factors that may predict long-term outcomes. Therefore, the purpose of this study was to evaluate how certain sociodemographic factors may influence mortality and the need to undergo lower extremity amputation in patients with Charcot. Methods: Following institutional board approval, all patients from 2015-2021 with a diagnosis of Charcot Foot were queried using hospital electronic medical records. Demographics collected included sex, age, race, and insurance coverage. Outcomes recorded were the need to undergo major amputation and mortality rate. Statistical analysis was then run to determine if sex, age, race, and insurance coverage was associated with increased risk of needing a major amputation or death. Results: From 2015-2021, 80 Charcot patients with a mean age of 60 (Range, 84-32) were identified. Of these patients, 58 were male, 26 were female, 71 were white, 3 were African American, and 6 were identified as other. In our cohort, 47 patients had government funded insurance and 33 had private insurance. Amputation occurred in 22 patients and death in 15. Government funded insurance (RR: 9.8, 95% CI:1.4-71.1, P = 0.0236) and age over 65 was associated with an increased risk of death (RR: 2.5, 95% CI: 1.02 to 6.17; P = 0.044). No statistically significant increased risk of death or amputation was found in white, African American, male, or female patients. Government insurance was also not associated with an increased risk for amputation (Table 1). Conclusion: Charcot Neuroarthropathy is associated with high rates of morbidity and mortality. In our cohort, there was an increased risk of mortality in patients with government funded insurance and patients over the age of 65. Further investigation exploring the role of sociodemographic factors is warranted.